IMPLEMENTASI KEBIJAKAN KEMERDEKAAN BELAJAR DALAM PROSES PEMBELAJARAN DI KAMPUS IAKN KUPANG-NTT - Hendrik A.E. Lao; Yandri Yusuf Cornelis Hendrik (Jurnal Dedikasi Pendidikan, 2020)
AbstractThe purpose of this study was to analyze the implementation of the policy of the learning freedom in the learning process at the collage of IAKN Kupang. The method used in this research is a qualitative approach and data sources totaling 5 people, namely 3 lecturers and 2 students, with data collection techniques namely interviews and analyzed with data triangulation techniques.The results of the research related to the implementation of freedom of learning in the learning process at the collage of IAKN Kupang, it can be concluded that the implementation of learning freedom that occurs in the learning process that lecturers and students are still accustomed to conventional learning that positions lecturers as the main actors while students are considered as objects of learning. Student success is measured by the extent to which students have mastered learning material not the extent to which students have undertaken the learning process. Therefore, mastery of subject matter is not the end of the teaching process, but only as a goal between the formation of broader behavior.Keywords: policy implementation; freedom of learning; learning process